An Assessment/Investigation on Malaysia School Heads’ Technology Leadership Inclinations and Activities. - Yusup, Hashim; Yusri, Yusup (2013)
A study was conducted on 120 schools heads in Malaysian schools in June 2013 to identify their inclinations and technology activities using NETS-A. Survey questions consisting of 36 items were distributed and 60% returned the questionnaires. The result of the study showed that the Teaching and Learning standard has the highest score while Social, Legal and Ethical Issues has the lowest score. Primary school outperforms secondary schools in every Educational Technology Standard. Similarly, rural area schools outperform urban schools in every standard.